Sputtering of thin films - Musil, Jindrich (Kovine zlitine tehnologije, 1997)
The sputtering and evaporation of solid materials are fundamental physical processes now currently used in the Physical Vapour Deposition (PVD) of thin films. Up to the mid 70's, however, evaporation dominated over sputtering in PVD technologies. It was due mainly to a verya low sputter deposition rate of the film and relatively high pressures (> 1 Pa) needed to sustain the sputtering discharge. The breakthrough arrived when the planar magnetron was discovered by Chaplin (1) in 1974. From this moment a very strong development of the sputtering method started. In this paper the main milestones reached in the development of sputtering discharges and deposition of thin films are given. Also, the present trends of the next developments in this field which will meet the requirements of new advanced technologies in the first years of the 21st century are outlined.
Keywords: naparevanje; naprševanje; tanke plasti; magnetroni; plazma